Rise and shine a novel - Quindlen, Anna (Random House, 2006)
A novel about two sisters, the true meaning of success, and the qualities in life that matter most. It's an otherwise ordinary Monday when Meghan Fitzmaurice's perfect life hits a wall. A household name as the host of the country's highest-rated morning talk show, Meghan cuts to a commercial break--but not before she mutters two forbidden words into her open mike. In an instant, it's the end of an era, not only for Meghan, who is unaccustomed to dealing with adversity, but also for her younger sister, Bridget, a social worker in the Bronx who has always lived in Meghan's long shadow. The effect of Meghan's on-air truth telling reverberates through both their lives, affecting Meghan's son, husband, friends, and fans, as well as Bridget's perception of her sister, their complex childhood, and herself.--From publisher description.